2019
DOI: 10.1186/s13018-019-1409-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological risk factors associated with dislocation after bipolar hemiarthroplasty of the hip in patients with femoral neck fractures—a nested case-control study

Abstract: BackgroundThe relationship between preoperative hip measurements and dislocation after bipolar hemiarthroplasty is presently unclear. In the current study, we investigated the morphological risk factors associated with dislocation after bipolar hemiarthroplasty of the hip in patients with femoral neck fractures.MethodsBetween January 2011 and June 2017, a nested case-control design study was used to analyze the risk factors for dislocation in 348 patients who had undergone bipolar hemiarthroplasty because of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Decreased CE angle was associated with a shallower and more vertical acetabulum, leading high risk of dislocation. Similarly, Zhang et al 14 reported that HA patients with a CE angle ≤45.4°or an acetabular depth ≤ 19.12 mm were more likely to suffer dislocation. A Korean study also pointed that defining dislocation as the existence of a CE angle >44°had a sensitivity of 81.3% and a specificity of 76.0% in hemiarthroplasty.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Decreased CE angle was associated with a shallower and more vertical acetabulum, leading high risk of dislocation. Similarly, Zhang et al 14 reported that HA patients with a CE angle ≤45.4°or an acetabular depth ≤ 19.12 mm were more likely to suffer dislocation. A Korean study also pointed that defining dislocation as the existence of a CE angle >44°had a sensitivity of 81.3% and a specificity of 76.0% in hemiarthroplasty.…”
Section: Discussionmentioning
confidence: 90%
“…8,11 Several studies have identified risk factors for dislocation in patients after undergoing hip HA. [12][13][14] However, conclusive evidence is rare and some studies have presented contradicting results. Generally, risk factors were classified into patient factors, surgical factors, and morphological factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have stated that the incidence of dislocation is related to the small acetabular depth and small acetabular depth-width ratio. The elderly patients with a center-edge angle of ≤ 45.4° (p < 0.001) or an acetabular depth of ≤ 19.12 mm (p< 0.001) were susceptible to experience dislocation after BHA [7]. A comprehensive review by Jones et al explained several factors related to HA dislocation, including patient cognition, preceding surgery failure, delay to surgery, types of surgical approach, and the femoral offset [8].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors maintain that patients with smaller lateral centre-edge angle (LCEA) and smaller acetabular depth are more likely to suffer this complication. 17 20 Further, an offset discrepancy seems to be a known and accepted risk factor for dislocation. 13,19…”
Section: Introductionmentioning
confidence: 99%